+0

0
113
1
+98

The standard form of the equation of a circle is (x−3)2+(y−1)2=16.

What is the general form of the equation?

x2+y2−6x−2y−6=0

x2+y2+6x+2y+26=0

x2+y2−6x−2y−26=0

x2+y2+6x+2y−6=0

CrazyDaizy  Jun 6, 2017
edited by CrazyDaizy  Jun 6, 2017
Sort:

#1
+4784
+1

(x - 3)2 + (y - 1)2   =   16

To get this into general form, we need to multiply out   (x - 3)2   and   (y - 1)2 .

(x - 3)(x - 3)  +  (y - 1)(y - 1)   =   16                      First, let's just do (x - 3)2 .

x2 - 3x - 3x + 9  +  (y - 1)(y - 1)   =   16                Now, let's do (y - 1)2 .

x2 - 3x - 3x + 9  +  y2 - 1y - 1y + 1   =   16          Subtract 16 from both sides of the equation.

x2 - 3x - 3x + 9  +  y2 - 1y - 1y + 1 - 16   =   0     Combine like terms.

x2 - 6x + y2 - 2y - 6 = 0          Rearrange.

x2 + y2 - 6x - 2y - 6 = 0

hectictar  Jun 6, 2017

### 26 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details